Sharp objects [compact disc, unabridged] : a novel - Flynn, Gillian, 1971- (Books on Tape, 2006)
Fresh from a brief stay at a psych hospital, Camille's first assignment from the second-rate daily paper where she works brings her reluctantly back to her hometown to cover the murders of two preteen girls. Clues keep leading to dead ends, forcing Camille to unravel the psychological puzzle of her own past to get at the story. Dogged by her own demons, Camille will have to confront what happened to her years before if she wants to survive this homecoming.